The relationship of work stress and employee's job performance / Nur Nashreena Aliya Mohd Ghani - Mohd Ghani, Nur Nashreena Aliya (Faculty of Business And Management, 2016)
The purpose of this research is to identify the relationship of work stress and employee job performance in one of the local authorities in Malaysia which is Majlis Perbandaran Kuantan (MPK). The independent variable for this study, Work Stress had been measured by three factors such as Work Overload, Interpersonal Conflict, and Work Environment. For the dependent variable, Employee Job Performance been measured by Commitment. Using questionnaire as the research instrument. The questionnaires were distributed to 65 respondents in Majlis Perbandaran Kuantan (MPK) by using the simple random sampling technique. The data was analyzed using Statistical Package of Social Science (SPSS) software version 23.0. There are several test had been run such as reliability analysis, regression analysis, and correlation analysis to analyze all the data. The findings of the data are demonstrated that all the factors can be used to measure the relationship of work stress and employee job performance at Majlis Perbandaran Kuantan (MPK). Based on the findings also shown the most influential factor Of Work Stress towards employee's job performance at this organization was Work Environment